A Model of Buddhist Subject Management by Online Creative Media of Moral Teaching Monks in Schools, Khon Kaen Province - Tenissara, Sukanda; Saengsai, Prayoon; Ruangsan, Niraj (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) study the current and desired conditions of Buddhist subject learning management using online creative media by moral teaching monks in schools in Khon Kaen Province; 2) develop a learning management model; 3) implement and evaluate the developed model; and 4) assess the appropriateness and usefulness of the developed model. This study employed a Research and Development (R&D) methodology, conducted in four phases. The sample consisted of 328 school administrators and moral teaching monks selected from 905 schools in Khon Kaen Province. Research instruments included questionnaires, semi-structured interviews, and evaluation forms to assess the appropriateness, feasibility, and usefulness of the model. The research findings revealed that: 1) The current conditions of learning management were rated at a high level overall ( = 3.58), while the desired conditions were also rated at a high level overall ( = 4.49) Priority needs ranking showed that flexible learning time management ranked highest, followed by educational technology utilization skills. 2) The developed learning management model consisted of five key components and employed the PDCA quality cycle as the mechanism for implementation. 3) The trial implementation showed that adapting assessment methods to include worksheets or other instructional media as part of special activity scores, along with adding knowledge sheets and conducting pre-and-post tests, enhanced learning effectiveness. 4) Evaluation by stakeholders indicated that the developed model was highly appropriate, feasible, and useful in all components.